Calibration of Fermi Velocity to Explore the Plasmonic Character of Graphene Nanoribbon Arrays by a Semi-Analytical Model - Talia Tene; Marco Guevara; Edwin Viteri; Alba Maldonado; Michele Pisarra; Antonello Sindona; Cristian Vacacela Gomez; Stefano Bellucci (Nanomaterials, 2022)
We present an analysis of the electronic and plasmonic behavior of periodic planar distributions of sufficiently wide graphene nanoribbons, for which a thorough ab initio investigation is practically unfeasible. Our approach is based on a semi-analytical model whose only free parameter is the charge carrier velocity, which we estimate by density-functional theory calculations on graphene. By this approach, we show that the plasmon resonance energies of the scrutinized systems fall in the lower THz band, relevant for optoelectronic and photonic applications. We further observe that these energies critically depend on the charge carrier concentration, ribbon width, electron relaxation rate, and in-plane transferred momentum angle, thus, suggesting a tunability of the associated light-matter modes.